Educational aspects in mountain tourism - An old or a new paradigm? - Gheorghe LUCACIU; Simona-Corina LUCACIU; Ovidiu DULFU; Paul-Florian DRAGOȘ (Editura Universităţii din Oradea, 2023)
The approach to mountain tourism from an institutional position by including this activity in the Education Plan of the Faculty of Physical Education and Sport, occurred many years ago (since 1965) and due to the impact of this activity on a growing number of people from more diverse categories, it was motivated by the multiplication of options in terms of professional inclusion but also the capitalization of possible educational effects.On the other hand, we believe that we must ask ourselves if the aims of the discipline "Internship in tourism activities" subscribe to the components of the instructional-educational process specific to the higher education of physical education and sports. The attempt to give an answer to this question represented the foundation of this study.